New biomarkers of injury, inflammation and remodeling in the differential diagnosis of heart failure types - E. K. Serezhina; A. G. Obrezan (Российский кардиологический журнал, 2021)
Heart failure (HF) is a global pandemic that is steadily increasing in prevalence. Currently, based on the left ventricular ejection fraction, three types of HF are distinguished. A theory was created that the HF pathophysiology is based on two processes: systolic and diastolic myocardial dysfunction. Due to the heterogeneity of HF, it is necessary to develop methods for differential diagnosis of its types to ensure adequate risk assessment and patientcentered therapy. Taking into account the objectivity, reproducibility, and high sensitivity of biomarkers of injury, inflammation, and myocardial remodeling, these parameters can be used for these purposes. To date, many biological molecules have been identified, such as sST2, Gal-3, GDF-15, FABP, IGFBP, micro-ribonucleic acid, sensitivity and specificity of which are superior to natriuretic peptides and high sensitivity troponins used today, and are already being introduced into clinical practice. At the same time, it is advisable to conduct additional prospective studies for a more objective assessment of diagnostic significance and the potential of its use in routine diagnosis and prognosis of heart failure.